1992
DOI: 10.1002/j.1460-2075.1992.tb05485.x
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of human platelet-derived growth factor BB.

Abstract: The crystal structure of the homodimeric BB isoform of human recombinant platelet‐derived growth factor (PDGF‐BB) has been determined by X‐ray analysis to 3.0 A resolution. The polypeptide chain is folded into two highly twisted antiparallel pairs of beta‐strands and contains an unusual knotted arrangement of three intramolecular disulfide bonds. Dimerization leads to the clustering of three surface loops at each end of the elongated dimer, which most probably form the receptor recognition sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
144
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(148 citation statements)
references
References 57 publications
4
144
0
Order By: Relevance
“…Finally, direct and competitive ELISAs were performed with serum samples from 29 consecutive patients with SLE (SLE Disease Activity Index range [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The distribution of PDGFRa binding in SLE serum was comparable to that in healthy control serum, as determined by direct ELISA with PDGFRa-His.…”
Section: Epitope Specificity Of Anti-pdgfra Autoantibodies In Sscmentioning
confidence: 99%
“…Finally, direct and competitive ELISAs were performed with serum samples from 29 consecutive patients with SLE (SLE Disease Activity Index range [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The distribution of PDGFRa binding in SLE serum was comparable to that in healthy control serum, as determined by direct ELISA with PDGFRa-His.…”
Section: Epitope Specificity Of Anti-pdgfra Autoantibodies In Sscmentioning
confidence: 99%
“…Daopin et al (1992) showed that three disulfides present in &nerve growth factor and transforming growth factor-6 can be superimposed to within 1 A , even though only two other residues were conserved in these two topologically related structures. Another predominantly &sheet cytokine, platelet-derived growth factor, may also show a similar arrangement of disulfides, although detailed comparisons have not yet been presented (Oefner et al, 1992). It is clear that the role of the disulfides in preserving structural integrity of these two classes of cytokines must be completely different.…”
Section: Disulfide Bondsmentioning
confidence: 99%
“…All VEGFs are antiparallel, cystine-knot polypeptide dimers that are covalently linked by two intermolecular disulfide bonds (16)(17)(18)(19). In VEGF-C and VEGF-D, this VEGF homology domain is flanked by C-and N-terminal propeptides that are sequentially cleaved, giving rise to VEGF homologs with distinct functions.…”
mentioning
confidence: 99%